A Phenomenological Study on the Transition and Adjustment Process of Out-of-School Youth in a Four-Year University - Jae-Ra Jang; Min-Jeong Choe; Hang Jo (Jounral of Educational Therapist, 2026)
This study aimed to explore the psychological dynamics and essential meanings experienced by out-of-school youth in the process of transitioning to and adjusting to four-year universities after passing the high school equivalency exam. Semi-structured 1:1 in-depth interviews were conducted with eight out-of-school youth attending four-year universities. Data were analyzed using Giorgi’s phenomenological method. Five core themes emerged from 36 meaning units and 14 focal meanings: "The self longing for recovery through college", "The inescapable scarlet letter of a dropout", "The fiercely struggling examinee outside the school system", "My newly written narrative", and "Growing from inside rather than outside". These findings suggest that their college transition is a dynamic process of reconstructing positive self-identity and career adaptability, not merely a return to formal education. Based on these findings, counseling interventions and support strategies for successful college adjustment were discussed.